Antipsychotic-induced Tardive dyskinesia: from biological basis to clinical management. (2nd September 2017) - Salem, Haitham; Pigott, Teresa; Zhang, Xiang Y.; Zeni, Cristian P.; Teixeira, Antonio L.
ABSTRACT: Introduction : Tardive dyskinesia (TD) is a chronic and disabling movement disorder with a complex pathophysiological basis. A significant percentage of patients does not receive correct diagnosis, resulting in delayed or inaccurate treatment and poor outcome. Therefore, there is a critical need for prompt recognition, implementation of efficacious treatment regimens and long-term follow up of patients with TD. Areas covered : The current paper provides an overview of emerging data concerning proposed pathophysiology theories, epidemiology, risk factors, and therapeutic strategies for TD. Expert commentary : Despite considerable research efforts, TD remains a challenge in the treatment of psychosis as the available strategies remain sub-optimal. The best scenario will always be the prophylaxis or prevention of TD, which entails limiting the use of antipsychotics.